Amylopectin staling of cooked milled rices and properties of amylopectin and amylose - Villareal, Corazon P.; Hizukuri, Susumu; Juliano, Bienvenido O. (Wiley, 1997)
Starches of waxy rices that showed varietal differences in hardness testing of cooked rice after amylopectin staling and high‐amylose content (AC) rices differing in gel consistency (GC) and starch gelatinization temperature (GT) were studied to determine the factors related to varietal differences in amylopectin staling of cooked rice. Intermediate‐ and high‐GT starches showed greater amylopectin staling of gelatinized rice by hardness testing values or differential scanning calorimetry (DSC) endotherm than did low‐GT starches in both waxy and nonwaxy rices. Isoamylase‐debranched amylopectins of waxy rices differed in the ratio of weight‐average degree of polymerization (DPw) fractions, but these fraction ratios were not simply related to differences in amylopectin staling of cooked rice. Among high‐AC rices, amylopectin from low‐GT starch was confirmed to have higher iodine affinity (2.3–2.5%) than amylopectin from intermediate‐GT starches (1.7–1.8%), regardless of GC. Within high‐AC starch of the same GT type, soft‐GC rice corresponded with more A + B1 DPw 16–18 and less B3 DPw 150–200 fractions of debranched amylopectin and low DPw of amylose. Amylopectin of amylose extender mutant of IR36 was confirmed to have a longer chain length than ordinary rice amylopectin: the debranched amylopectin has more B2 DPw 47–51 fraction, less A + B1 DPw fraction, but no B4 fraction with DPw > 200. Only high‐AC amylopectin had debranched fraction with DPw >120.